The use of logotherapeutic techniques in the identification and intervention stages of treatment with persons with substance use disorder (2016)
Logotherapy was developed by Viktor Frankl in the 1930s as the Third Viennese School of Psychotherapy (the first is Psychoanalysis by Sigmund Freud and the second is Individual Psychology by Alfred Adler). It offers useful and effective intervention techniques which can be carried out in persons with substance use disorder. This is particularly remarkable in the African context, where long term therapy is not readily feasible due to the polarized nature of the pervading culture. In demonstrating the stance of logotherapy, the paper examined the prevalence of substance use disorder and how it has been conceptualized as a part of the mass neurotic triad of modern times. It illustrated logotherapy techniques in a stepwise fashion and highlighted some studies in order to establish the effectiveness of logotherapy in the identification and intervention stages of treatment with persons suffering from substance use disorder.